Hjemmehjælp og hjemmehjælper i forandringens arena - Lewinther, Mra (Kvinder, Køn & Forskning, 1997)
This article analyzes how home helpers from a rural and an urban municipality have reacted to the organizational changes that have taken place in the home care services. The changes are based on a model of self-directed groups that was employed in various production industries that had as its objective both improving worker job satisfaction and productivity. The home helpers felt that the changes were partially beneficial. They appreciated the fact that they could work in groups an have colleagues they could discuss work related problems with. On the other hand, they were concerned about the instrumentalization of their work that accurred at the same time; it became more governed by regulations and narrowly defined tasks rather than clients's needs. The article discusses how industry production differs from home care and discusses the existence of two cultures: that of traditional women's domestic work and caring and that of medical-bureaucratic organization and how these have clashed around the organizational changes.